Tracing dynamic behaviours in distributed learning communities - Ramos, Fernando (2002)
Experience and research reports agree that the timely contribution of participants, namely students and tutors, in distributed learning communities, is a key factor for the achievement of the collective and individual learning aims. The technological support required for Internet based distributed learning communities provides means to effectively trace the behaviour of each participant and analyse it according to a pre-defined time pattern reference, enabling the automated early detection of some unwanted disturbances and enabling the execution of procedures aiming at its correction. This paper presents and discusses a conceptual framework for tracing dynamic behaviour of participants in Internet based distributed learning communities, and presents work in progress related to its implementation.